Reduction and Fixation of Unstable Fractures of the Zygomatic Arch: Report of a Series of Cases - Cavalcante, Josuel Raimundo (J Surg Tech Case Rep, 2015)
BACKGROUND: This study evaluated a series of cases of fracture in the zygomatic arch with displacement of the fractured segment. MATERIALS AND METHODS: This prospective cohort study was conducted between May 2008 and February 2009. The study sample which consist of 10 patients of both genders with fractures in the zygomatic arch. The collection instrument included a specific sheet with data concerning the patient's age, cause, side of the fracture, type of treatment performed, recurrence and presence of lesions in the facial nerve. The radiographic indices of Waters and Hirtz were used. The data were presented by means of descriptive statistics (absolute and percentage distributions). RESULTS: Most of the patients were male (90.0%), the most frequent etiology was a motorcycle accident (70.0%) and the left side was more affected (60.0%). There was no recurrence in any of the patients examined; however, 1 patient had a lesion in the facial nerve. The treatment performed for all patients was reduction and fixation with titanium miniplates. CONCLUSION: Fractures in the zygomatic arch are more frequent in young male individuals and the most common cause is a motorcycle accident, with the use of miniplates constituting an effective treatment without recurrence.